The The Relationship between Street Furniture Arrangement and Pedestrian Comfort in the Ngurah Rai Corridor, Gianyar - Cipta Utari, Cokorda Istri Arina; Hartawan, I Putu (Journal of A Sustainable Global South, 2023)
Elements of street furniture are an integral part of other urban planning elements that give a city a special image and character that can enhance the identity of the city itself. The city of Gianyar is a commercial area, which is precisely along Jalan Ngurah Rai which is the center of trade, government and recreation. As a commercial area, so the physical quality is very important in this area. As a commercial city, this area has not fully improved and improved existing facilities and infrastructure, such as the arrangement of street furniture elements, which are one of the supporting elements of a public space. This can be achieved by designing street furniture that has good function and quality and is integrated with other street face elements to avoid environmental incoherence. The need for street furniture as a public open space facility is increasingly being felt and needed by the community, especially for pedestrians as a supporting element for friendly public spaces in Gianyar City to provide comfort for its users. The research method uses a descriptive method with a qualitative approach. A qualitative approach is carried out in the process of observing and analyzing elements of street furniture and pedestrian comfort in the Ngurah Rai corridor, Gianyar. This research aims to create and improve city infrastructure that is comfortable and friendly for pedestrians of various groups, both in terms of access, aesthetics, security, and safety and comfort.